2007
DOI: 10.1007/s10490-006-9024-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the practical utility of Wong’s emotional intelligence scale in Hong Kong and mainland China

Abstract: Emotional intelligence (EI) has been an emerging topic for psychological, educational, and management researchers and consultants in recent years. However, there is a lack of scientifically valid measures of this concept, especially for those that have practical utility in the Asian context. Recently, a 40-item forced-choice instrument was developed for Chinese respondents in Hong Kong. We collected data in three studies to further test the practical utility of this instrument in Hong Kong and mainland China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 20 publications
3
61
0
5
Order By: Relevance
“…An example of ability pairs is "ability to motivate oneself to face failure positively versus ability to learn to create an artistic object (e.g., pottery, painting)." Apart from the developmental samples, subsequent studies using Chinese samples have cross-validated the acceptable reliability and convergence, and discriminant and predictive validities of the scale (Wong, Wong, and Law 2007).…”
Section: Measure Of Emotional Intelligence (Ei)mentioning
confidence: 99%
“…An example of ability pairs is "ability to motivate oneself to face failure positively versus ability to learn to create an artistic object (e.g., pottery, painting)." Apart from the developmental samples, subsequent studies using Chinese samples have cross-validated the acceptable reliability and convergence, and discriminant and predictive validities of the scale (Wong, Wong, and Law 2007).…”
Section: Measure Of Emotional Intelligence (Ei)mentioning
confidence: 99%
“…Emotional intelligence By using Wong & Law"s, 2002 [42] WLEIS cited by (Libbrecht, Lievens, Beucklaer & Rockstuhl,2014) [30], emotional intelligence were used.Basically emotional intelligence comprised of four dimensions and each scale regarding each dimension consists of four questions. Selfemotional appraisal (SEA) Will be measured by asking I have a good wisdom of why I have definite feelings most of the time, Others Emotions Appraisal (OEA), I always know my friends" emotions from their actions, Use of Emotion (UOE) I always set objective for myself and then try my best to accomplish them, Regulation of Emotion (ROE) I am able to control my annoyance so that I can handle difficulties rationally.…”
Section: 34mentioning
confidence: 99%
“…Existe un consenso general que dice que la inteligencia emocional es la habilidad de los individuos de lidiar con las emociones (Salovey y Mayer, 1990;Law, Wong y Song, 2004;Mayer, Caruso y Salovey, 2000;Wong, Law y Wong, 2004a;Wong, Wong y Law, 2007) y que es tan o más importante que el coeficiente intelectual en la vida de negocios y en la carrera profesional (Erkus, 2008;Goleman, 1995 Mayer, 1990;Law, Wong and Song, 2004;Mayer, Caruso and Salovey, 2000;Wong, Law and Wong, 2004ª;Wong and Law, 2007), which is as important or more important than the intellectual coefficient in a world of business and in a professional carrer (Erkus, 2008;Goleman, 1995 Wong and Law, 2002, was used, having a total sample of 218 participants. This instrument has been proved and validated, and as a result, it has been concluded that it can be used in management, leadership and organizational behaviour areas (Aslan and Erkus, 2008) (Salovey et Mayer, 1990 ;Law, Wong et Song, 2004 ;Mayer, Caruso et Salovey, 2000 ;Wong, Law et Wong, 2004;Wong, Wong et Law, 2007) ce qui est aussi voire plus important que le coefficient intellectuel dans le domaine des affaires et dans la carrière professionnelle (Erkus, 2008 ;Goleman, 1995 (Aslan et Erkus, 2008 dice que cuatro de cada cinco compañías están tratando de incrementar la inteligencia emocional de sus empleados como un medio de incrementar ventas, mejorar el servicio al cliente (Cavelzani et al, 2003) y asegurar que sus ejecutivos tengan un buen desempeño a nivel internacional.…”
Section: Inteligencia Emocional Sistema Financiero Colombiano Medicióunclassified
“…This instrument has been proved and validated, and as a result, it has been concluded that it can be used in management, leadership and organizational behaviour areas (Aslan and Erkus, 2008) (Salovey et Mayer, 1990 ;Law, Wong et Song, 2004 ;Mayer, Caruso et Salovey, 2000 ;Wong, Law et Wong, 2004;Wong, Wong et Law, 2007) ce qui est aussi voire plus important que le coefficient intellectuel dans le domaine des affaires et dans la carrière professionnelle (Erkus, 2008 ;Goleman, 1995 (Aslan et Erkus, 2008 dice que cuatro de cada cinco compañías están tratando de incrementar la inteligencia emocional de sus empleados como un medio de incrementar ventas, mejorar el servicio al cliente (Cavelzani et al, 2003) y asegurar que sus ejecutivos tengan un buen desempeño a nivel internacional. La inteligencia emocional sigue siendo materia de estudio y se ha encontrado que tiene una relación directa con el desempeño laboral (Cartwright y Pappas, 2008).…”
Section: Inteligencia Emocional Sistema Financiero Colombiano Medicióunclassified